INTERFACE SHEAR STRESS ANALYSIS AND INTERFACE SHEAR STRENGTH MEASUREMENT OF YTTRIA-STABILIZED-ZIRCONIA COATINGS - GONG ManFeng; QIAO ShengRu; MEI Fang (Jixie qiangdu)
The application performance of coatings are depended on their interface bonded condition when coatings are bonded with substrate,and the interface stresses of coatings directly influences on their strength properties. The equations about interface shear stress of coatings,which based on a model of interface restriction and uniformity strain theory,were deduced.These equations could be used to determine the interface shear strength of coatings. The accuracy of theory analysis and the effectiveness of testing method were further verified by experiment. The interface shear strength of yttria stabilized zirconia coatings was measured by a new tensile method. The coatings were discriminatively sprayed on three parts on specimens with different thickness,and which contributed to analyzing the relationship between coatings’ thickness and their strength properties.